Preliminary observations on waterfowl of Western Madagascar - Scott, Dafila; Lubbock, Joanna (Wildfowl, 1974)
A reconaissance was made to Madagascar to study waterfowl, particularly the rare Bernier's Teal Anas bernieri in the vicinity of the shallow saline Lake Bemamba. The habitat and behaviour of the teal and also of the Madagascar White-backed Duck Thalassornis leuconotus insularis are described. Estimates of numbers are given for other waterfowl, and a list of all birds seen. Two Madagascar White-backed Ducks and two Pygmy Geese Nettapus auritus were brought into captivity. Waterfowl in the area have declined in numbers and Bernier's Teal may perhaps be in danger of extinction. Lake Bemamba merits the formation of a reserve.